Sclerodermiform basal cell carcinoma: how much can we rely on dermatoscopy to differentiate from non-aggressive basal cell carcinomas? Analysis of 1256 cases - Husein Husein-ElAhmed (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: The behaviour of each basal cell carcinoma is known to be different according to the histological growth pattern. Among these aggressive lesions, sclerodermiform basal cell carcinomas are the most common type. This is a challenging-to-treat lesion due to its deep tissue invasion, rapid growth, risk of metastasis and overall poor prognosis if not diagnosed in early stages. Objective: To investigate if sclerodermiform basal cell carcinomas are diagnosed later compared to non-sclerodermiform basal cell carcinoma Method: All lesions excised from 2000 to 2010 were included. A pathologist classified the lesions in two cohorts: one with specimens of non-aggressive basal cell carcinoma (superficial, nodular and pigmented), and other with sclerodermiform basal cell carcinoma. For each lesion, we collected patient's information from digital medical records regarding: gender, age when first attending the clinic and the tumor location. Results: 1256 lesions were included, out of which 296 (23.6%) corresponded to sclerodermiform basal cell carcinoma, whereas 960 (76.4%) were non-aggressive subtypes of basal cell carcinoma. The age of diagnosis was: 72.78±12.31 years for sclerodermiform basal cell and 69.26±13.87 years for non-aggressive basal cell carcinoma (P<.0001). Sclerodermiform basal cell carcinomas are diagnosed on average 3.52 years later than non-aggressive basal cell carcinomas. Sclerodermiform basal cell carcinomas were diagnosed 3.40 years and 2.34 years later than non-aggressive basal cell carcinomas in younger and older patients respectively (P=.002 and P=.03, respectively). Study limitations: retrospective design. Conclusion: The diagnostic accuracy and primary clinic conjecture of sclerodermiform basal cell carcinomas is quite low compared to other forms of basal cell carcinoma such as nodular, superficial and pigmented. The dermoscopic vascular patterns, which is the basis for the diagnosis of non-melanocytic nonpigmented skin tumors, may not be particularly useful in identifying sclerodermiform basal cell carcinomas in early stages. As a distinct entity, sclerodermiform basal cell carcinomas show a lack of early diagnosis compared to less-aggressive subtypes of BCC, and thus, more accurate diagnostic tools apart from dermatoscopy are required to reach the goal of early-stage diagnosis of sclerodermiform basal cell carcinomas.